Laparoscopic management of a true broad ligament leiomyoma in a patient with advanced endometriosis and a solitary kidney - A case report and literature review - Vishal Bahall; Lance De Barry (Elsevier, 2022)
Leiomyomas are the most common benign tumours of the female genital tract, and almost always arise from the uterine myometrium. Although extrauterine leiomyomas are rare, they usually develop in sites such as the ovary, broad ligament, round ligament, cervix or abdominal wall. The broad ligament is the most common site of extrauterine leiomyoma involvement, and this unique clinical entity may prove to be a diagnostic or therapeutic challenge, particularly in patients with advanced endometriosis and distorted pelvic anatomy. Herein, we report the case of a large true broad ligament leiomyoma that was discovered during a total laparoscopic hysterectomy and bilateral salpingo-oophorectomy in a 47-year-old patient with stage IV endometriosis and a congenital left kidney and left ureter. This case highlights a rare occurrence of a true broad ligament leiomyoma, the challenges associated with preoperative diagnosis, and the laparoscopic approach to its management.